The objective prerequisites for transition of the Republic of Belarus to the restrictive state immunity doctrine - Yevmenchikovа, Оlga A. (Journal of the Belarusian State University. Law, 2021)
The article is devoted to the research of doctrine based approaches and court practice to regulation of jurisdictional state immunity. The author analyses the international court practice as well as the foreign court and arbitration practice regarding to jurisdictional state immunity application. Based on the results of the research the feasibility of transition of the Republic of Belarus to the restrictive state immunity doctrine is substantiated
Keywords: jurisdictional state immunity; absolute state immunity doctrine; restrictive state immunity doctrine; functional state immunity doctrine; European Court of Human Rights